An Exploration Of Leadership Styles And Their Impact On Employee Performance At ZESCO Limited, Zambia: - Mwambela, Able; Zulu, Bupe (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The study examined the influence of different leadership styles on employee performance within ZESCO Limited, Zambia. Its principal objective was to evaluate the impact of transformational, transactional, laissez-faire, and servant leadership styles on employee performance, with the ultimate goal of enhancing organisational effectiveness and overall employee performance. Design/methodology/approach: Using a mixed-methods approach, a structured questionnaire was disseminated to 300 employees, resulting in 156 valid responses. Through rigorous statistical analyses encompassing Pearson correlation and ANOVA, the research endeavoured to examine the correlations between various leadership styles and employee performance. The study scrutinised hypotheses pertaining to the impacts of transformational, transactional, laissez-faire, and servant leadership. Research Findings: The findings highlighted that both transformational (p=0.199, 0.013) and servant (p=0.000, 0.330) leadership styles significantly enhance employee performance, demonstrating notably strong positive correlations. Although the transactional leadership style exhibited a weakness (p =.048, 0.159), it still showed a statistically significant positive correlation with employee performance. In contrast, a hands-off approach to leadership (p=0.00, -0.370) was discovered to hinder employee performance significantly. The practical findings were consistent with existing literature, emphasising the importance of proactive and supportive leadership in influencing employee results. Theoretical Contribution/Originality: The research concluded that transformational and servant leadership are crucial for enhancing employee performance within ZESCO Limited. While transactional leadership has some benefits, its impact is less significant. On the contrary, laissez-faire leadership has a negative effect on performance. Recommendations involve the implementation of leadership development initiatives that concentrate on transformational and servant leadership, the improvement of performance evaluation systems, the introduction of ongoing feedback mechanisms, and the establishment of robust leadership succession planning.